AN INVESTIGATION OF TEACHER FEEDBACK ON STUDENTS' WRITING AND THEIR OPINION - Daud, Abdulhalim (2016)
The role of teacher feedback strategies may have important effect on students' progress in developing competence in a target language. This study aims at investigating the type of teacher feedback strategies, the reason of the use of those feedback strategies, students' opinion on those used feedback strategies and their effect on students' writing. This study is a qualitative case study involving a teacher and one class at one vocational high school in Bandung. The students were categorized into the high, middle and low achievers based on their writing. The data in this study were obtained from three sources, including observation, document (students' writing draft) and interview. Data were collected to be analyzed to find out what feedback strategies that the teacher used (Ferris & Hedgcock, 2005), teacher's reason in using those feedback strategies, students' opinion about their teacher feedback strategies and the effect of teacher's feedbacks on students' writing. The findings of this study show that the teacher uses several feedback strategies: indirect feedback, direct feedback, and commentary feedback in giving feedback on students' writing. The teacher feels that she has responsibility to give feedback on students' writing to guide students in writing while the students perceived that they got benefit from their teacher's feedback. Further, the decrease of students' writing errors from first to final draft confirm the students' and the teacher's belief about the importance of teacher feedback to help students to improve students' writing quality and accuracy. These results demonstrate that teachers' feedbacks in teaching writing play an important role to help students to develop competence in a target language and their awareness of how to organize their ideas in written form. Based on the results of this study, writing teachers were suggested to implement process approach in teaching writing in the school and give feedback on students' writing.